Influences of Gasoline Fuels on Waste Heat Recovery Potentiality of a Spark Ignition Engine - I. M., Yusri; R., Mamat; Azmi, W. H.; Awad, Omar I.; M. F., Othman; S. M., Rosdi (Indian Society of Education and Environment, 2017)
Objectives: In this study, evaluation of the potential of energy recovery in spark ignition engine using RON 95 gasoline fuels. Methods: The engine has been operated at a single engine speeds of 3500 RPM with 50% of Wide Throttle Open (WTO). The potential of energy recovery was measured by means of engine effective power, Water Heat Losses (WHL) and Exhaust Heat Losses (EHL). Findings: Comparative analysis of the experimental results showed an improvement of 1.16%, 2.12% and 3.08% in EHL at 75°C, 50°C and 25°C, respectively, by taking 120°C as the reference temperature of EHL. The results of the contour plot showed that a trade-off between the WHL and EHL. Conclusion: Higher proportions of energy losses can be utilised by considering both WHL and EHL.